Osteoarthritis and Frailty: Associations, Relevance, and Counter Solutions - Marks Ray (Journal of Aging Research And Healthcare, 2022)
Background Many older adults, including those who have acquired painful disabling osteoarthritis of one or more joints may be frail rather than obese as is often reported. Those older adults who are frail may acquire osteoarthritis in turn if they encounter excess joint stresses and injury. Aims This report sought to examine what has been published to date on both of these debilitating health states, namely osteoarthritis and frailty. Methods Reviewed were relevant articles published in ACADEMIC SEARCH COMPLETE, PUBMED, WEB OF SCIENCE, SCOPUS and GOOGLE SCHOLAR regardless of time period but that focused on osteoarthritis and frailty related topics. The focus was on ascertaining how these two conditions might interact among community-dwelling older adults and whether more should be done specifically to mitigate any potentially preventable ‘frailty’ induced negative health impact among this group. Results Older adults with osteoarthritis living in the community may suffer from both osteoarthritis and frailty. Those that do are at high risk for disability and injury and should be targeted more effectively. Conclusion Timely and concerted efforts are needed to offset frailty correlates as well as excess osteoarthritis disability among community dwelling older adults.
Keywords: Frailty